The International Conferences on Applied Science and Health (ICASH): Efforts and Commitments in Translating Research Results into Policy and Practices, for a Better Society - Dyah Anantalia Widyastari; Doni Marisi Sinaga; Canggih Puspo Wibowo; Pamuko Aditya Rahman; Hafizh Muhammad Noor; Dimas Sondang; Tiara Fatmarizka; Dwina Gustia Diary; I Gusti Ngurah Edi Putra; Maretalinia; Marina Ayu Viniriani; Monita Destiwi; Galih Albarra Shidiq; Ivana Aprilia Pratiwi; Made Dian Shanti Kusuma; Ni Wayan Kesari Dharmapatni; Mahendrawan Nugraha Aji Pratama; Ary Norsaputra; Andi Pancanugraha; Febrian Hendra Kurniawan; Wahyu Manggala Putra; Rifqi Abdul Fattah; Puput Kusumawardani Moehas; Ricky Alexander Samosir; Andang Adi Fitria Hananto; I Gusti Ngurah Agastya; Taufik Eko Susilo; Pichpisith Pierre Vejvisithsakul; Donny Nauphar; Ariestya Indah Permata Sari; Andrew John Macnab (GHMJ (Global Health Management Journal), 2019)
-